2008
DOI: 10.1186/1753-2000-2-33
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of genetic variants in genes of the endocannabinoid system with anorexia nervosa

Abstract: Background: Several lines of evidence indicate that the central cannabinoid receptor 1 (CNR1) as well as the major endocannabinoid degrading enzymes fatty acid amide hydrolase (FAAH), Nacylethanolamine-hydrolyzing acid amidase (NAAA) and monoglyceride lipase (MGLL) are implicated in mediating the orexigenic effects of cannabinoids. The aim of this study was to analyse whether nucleotide sequence variations in the CNR1, FAAH, NAAA and MGLL genes are associated with anorexia nervosa (AN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 55 publications
(68 reference statements)
0
28
3
Order By: Relevance
“…The authors found a significant increase in the frequency of both polymorphisms in AN and BN patients, a result in sharp contrast with the previous findings by Muller et al [89] that showed a lack of association of these polymorphisms with AN. Additionally, Monteleone et al [91] found a synergistic effect of the two polymorphisms in AN but not in BN.…”
Section: Cannabinoids and Eating Disorderscontrasting
confidence: 56%
See 2 more Smart Citations
“…The authors found a significant increase in the frequency of both polymorphisms in AN and BN patients, a result in sharp contrast with the previous findings by Muller et al [89] that showed a lack of association of these polymorphisms with AN. Additionally, Monteleone et al [91] found a synergistic effect of the two polymorphisms in AN but not in BN.…”
Section: Cannabinoids and Eating Disorderscontrasting
confidence: 56%
“…However, upon dividing the samples to restricting and binging/purging subtypes of AN, the data analysis revealed a preferential transmission of different alleles in each of the subtypes, suggesting restricting AN and binging/purging AN may be associated with different alleles of the CNR1 gene [88]. However, a subsequent study involving up to 91 German AN trios (patient Dis Disord, 2017 doi: 10.15761/JDD.1000103 with AN and both biological parents) was unable to confirm these results, nor did it show an association for any of 15 single nucleotide polymorphisms representative of regions with restricted haplotype diversity in FAAH, NAAA, and MAGL genes [89].…”
Section: Cannabinoids and Eating Disordersmentioning
confidence: 65%
See 1 more Smart Citation
“…Genetic polymorphisms in the CNR1 gene have been associated with basal metabolic index, obesity and various metabolic parameters (Aberle et al, 2007;Baye et al, 2008;Benzinou et al, 2008;Gazzerro et al, 2007;Jaeger et al, 2008;Peeters et al, 2007;Russo et al, 2007), however some negative studies have also been reported (Aberle et al, 2007;Lieb et al, 2009;Muller et al, 2007). Significant association of polymorphisms in CNR1 with anorexia nervosa and bulimia nervosa have also been reported (Monteleone et al, 2009;Siegfried et al, 2004), despite one negative report (Muller et al, 2008). Based on these many significant findings, we hypothesized that CNR1 might be associated with antipsychotic-induced weight gain.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, mixed findings involving the overtransmission of cannabinoid receptor 1 ( CNR1 ) variants in AN have been reported, 152,153 and preliminary case-control findings need replication. 154 As mentioned in the linkage section, preliminary results involving the OPRD1 gene have been reported in AN, 66,67 whereas opioid receptor mu 1 gene ( OPRM1 ) has been implicated in hedonic eating in one study with 300 participants.…”
Section: Molecular Genetic Studies Of Eating Disordersmentioning
confidence: 99%